A study to assess valvular heart disease in a tertiary care hospital: a single centre finding - Ghogale, Prakash R.; Wanjari, Shishir K.; Singh, Daneshwar; N., Hanumanth; Mendhe, Harshal G. (International Journal of Advances in Medicine, 2019)
Background: Diseases of the heart valves constitute a major cause of cardiovascular morbidity and mortality worldwide with an enormous burden on healthcare resources. The present study was undertaken to study incidence and demography of valvular heart disease, to assess echocardiography and colour doppler findings of patients with valvular heart disease and to find out complications in patients with valvular heart disease. Methods: A hospital based longitudinal case study was undertaken at medicine department of Dr. V.M. Government Medical College, Solapur, Maharashtra, India for a period of two years. One hundred and twenty-four (124) patients attending OPD participated in the study. Results: In the present study, out of 124 patients, mitral valve was most commonly involved, 105(84.67%) and the least common involved was tricuspid 1(0.81%). The most common aetiology was rheumatic origin 75(94.94%). In the present study the most common complication was pulmonary hypertension 69(55.65%), followed by congestive cardiac failure (33.87%), acute pulmonary edema (12.09%), infective endocarditis (4.84%), cerebrovascular accident (4.03%), left atrial thrombus (3.23%) and death (3.23%). Conclusions: Multiple valves were affected in more than a third of all cases, although recent research in India continue to demonstrate a declining trend in the prevalence of RHD, rheumatic involvement is still the dominant form of valvular heart disease in India.